x= 5 + 3t

y = -2 + 4t

(THESE ARE PARAMETRIC EQUATIONS.)

x = 5 + 3t

3t = x - 5

t = (x - 5) / 3

Now substitute into y equation

y = -2 + 4((x - 5) / 3)

Multiply both sides by 3 to get

3y = -6 + 4x - 20

3y = 4x - 26

-4x + 3y = -26

So, x intercept is where y = 0

-4x + 0 = -26

x = -26/- 4 = 6.5

y intercept is where x = 0

0 + 3y = -26

y = -26/3 = - 8.67

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up